India : Equity Effects of Quality Improvements on Health Service Utilization and Patient Satisfaction in Uttar Pradesh State - Peters, David; Rao, Krishna; Ramana, G.N.V. (World Bank, Washington, DC, 2013)
This study investigates the impact of a health systems development project in Uttar Pradesh, India, on utilization of health services and patient satisfaction for the poor and lower caste members. The project began in July 2000, and introduced a range of reforms including management training, new staffing and service patterns, provision of essential drugs, and repair of equipment and facilities. The study uses a quasi-experimental design to compare changes in new outpatient visits and patient satisfaction at project and non-project health facilities. All public health facilities were scored according to health and economic conditions of the population and physical conditions of the facility, with the poorest scoring facilities selected for the project. A survey of service utilization, user perceptions, and economic status was conducted in 1999 at project facilities and an equal number of randomly selected control sites, stratified by level of facility: district and women's hospitals, community health centers (CHCs) and primary health centers (PHCs). A subsequent survey conducted in 2003 assessed changes in a systematically selected subset of the baseline sites. There was a consistent increase in mean monthly outpatient visits at all levels of project sites compared to controls, indicating that the project has improved overall utilization levels. Although patients from the poorest 40 percent of the population increased utilization at all types of facilities except the women's hospitals, the wealthiest 40 percent had larger increases at each level of facility. Lower caste members gained at all facilities relative to higher caste members. The project had a significantly positive impact on patient satisfaction at lower levels of facilities (CHCs and PHCs), but not for patients from the poorest 40 percent.